2006
DOI: 10.2337/dc05-2068
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Infection and Insulin Resistance in Healthy Middle-Aged Men

Abstract: OBJECTIVE -We hypothesized that burden of infection could be associated with chronic low-grade inflammation, resulting in insulin resistance. We aimed to study the effect of exposure to four infections on insulin sensitivity in apparently healthy middle-aged men (n ϭ 124).RESEARCH DESIGN AND METHODS -By inclusion criteria, all subjects were hepatitis C virus antibody seronegative. Each study subject's serum was tested for specific IgG class antibodies against herpes simplex virus (HSV)-1, HSV-2, enteroviruses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 43 publications
2
72
0
1
Order By: Relevance
“…It has been recently mentioned that healthy men with exposure to common pathogens (herpes virus types I and II, enteroviruses, and Chlamydia pneumonia), all of which are characterized by high frequency of exposure in the general population and persistent and chronic infection, might show increased fat mass and insulin resistance. The greater the exposure to these pathogens (inferred from serum antibody response), the higher the serum levels of inflammatory markers and the lower the insulin sensitivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently mentioned that healthy men with exposure to common pathogens (herpes virus types I and II, enteroviruses, and Chlamydia pneumonia), all of which are characterized by high frequency of exposure in the general population and persistent and chronic infection, might show increased fat mass and insulin resistance. The greater the exposure to these pathogens (inferred from serum antibody response), the higher the serum levels of inflammatory markers and the lower the insulin sensitivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Serum insulin levels were measured in duplicate by monoclonal immunoradiometric assay (IRMA or EASIA, Medgenix Diagnostics, Fleunes, Belgium). Intraassay and interassay coefficients of variation were similar to those previously reported [20,21]. Serum AST, ALT, and gammaglutamyltransferase were measured colorimetrically by automated tests (Roche Diagnostics GmbH).…”
Section: Analytical Determinationsmentioning
confidence: 98%
“…Basal blood samples were drawn at −30, −10, and −5 min, after which glucose (300 mg/kg body weight) was injected over 1 min starting at time 0, and insulin (Actrapid, Novo, Denmark; 0.03 U/kg) was administered at time 20 min. Additional samples were obtained from a contralateral antecubital vein up to 180 min, as previously published [20,21].…”
Section: Cross-sectional Studymentioning
confidence: 99%
“…pneumoniae infections have been associated with cardiovascular diseases, such as coronary heart diseases and acute myocardial infarction (8), suggesting that C. pneumoniae infection is involved in the development of atherosclerosis and its complications. Exposure to various pathogens, such as herpes simplex viruses 1 and 2, enteroviruses, and C. pneumoniae, was associated with decreased insulin sensitivity, and this effect became more significant when the pathogen burden increased, suggesting a role of chronic lowgrade inflammation in the development of insulin resistance (17). In another report, C. pneumoniae seropositivity showed a significant association with metabolic syndrome in men and women (18).…”
Section: Discussionmentioning
confidence: 93%
“…C. pneumonia infection may play a role in inducing both systemic inflammation and insulin resistance, and a possible link between these events could be an elevation in markers/mediators of inflammation such as CRP. A recent study has demonstrated a correlation between the C. pneumonia seropositivity index and insulin resistance (17), and another report showed a significant association with metabolic syndrome (18).…”
mentioning
confidence: 98%